Impression Management Strategy of Khofifah Indar Parawansa on Instagram Account @khofifah.ip - Emanuela Sitorus; Gatut Priyowidodo; Agusly Irawan Aritonang (Journal of Content and Engagement, 2024)
Impression management refers to an individual's need to present themselves acceptably to others, crucial for maintaining their image and achieving goals. This is particularly important for political actors in Indonesia as a democratic country. One political actor used impression management is Khofifah Indar Parawansa who needed to effectively manage her public image to secure a second term as Governor of East Java, particularly before the 2024 regional elections. This research analyzed Khofifah’s strategies on her Instagram account @khofifah.ip using descriptive quantitative content analysis methods. It examined verbal messages from 222 posts, including photos, videos, and text captions, between February 12, 2024, when Khofifah announced her candidacy, and May 9, 2024, when political dynamics changed. The strategies analyzed were ingratiation, self-promotion, intimidation, exemplification, and supplication. The research found that the most frequently used strategy by Khofifah was Ingratiation particularly the Other Enhancement tactic with the sub-indicator of Sympathy, emphasizing her efforts to gain public favor through various practices of sympathy tactics.